Effects of Lightness‐Location Congruency on Consumers' Purchase Decision‐Making. Issue 11 (November 2016) - Sunaga, Tsutomu; Park, Jaewoo; Spence, Charles
ABSTRACT: A considerable body of psychological and neuroscientific research has demonstrated the existence of robust sensory correspondences between various features, attributes, or dimensions of experience in different sensory modalities. Despite findings indicating the importance of sensory correspondences to human information processing, research on purchase decision‐making has not to date focused sufficiently on this phenomenon. The present study examines how the lightness of packaging colors, and the location of products on a display shelf interact to affect consumers' purchase decision‐making via perceived visual heaviness. As predicted, a display with light (dark) colored products positioned in the upper (lower) shelf positions increases shoppers' perceptual fluency and facilitates their visual search, thus leading to the suggestion that "light" (heavy) locations are most appropriate for light (dark) colored products. Moreover, the lightness‐location congruent display is shown to influence people's choice behavior positively as well. This research also demonstrates that when consumers consider the lightness (in terms of their weight) of the products, they are more likely to choose light (vs. dark) colored products located in the upper shelf positions. These results therefore demonstrate that consumers' purchase decision‐making may be promoted by in‐store environments designed to be congruent with their sensory correspondences.